2019
DOI: 10.1016/j.foodqual.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Measuring consumers attitudes towards health and taste and their association with food-related life-styles and preferences

Abstract: The purpose of the current study, was to apply and validate the factor structure of the Health and Taste Attitude Scales in an Italian adult sample of 1224 subjects, recruited on a national basis in order to characterise consumers' food-related attitudes with weak and strong connotations of health and taste. Both exploratory and confirmatory factor analysis were used to evaluate the factor structure of the three sub-scales of Health (General health interest, Light product interest, Natural product interest) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 59 publications
(79 reference statements)
4
65
0
1
Order By: Relevance
“…Product characteristics used by consumers to define food quality are not only numerous, but also dynamic, changing according to consumers' interests, concerns, needs, or knowledge. During recent years, consumers started to assign higher importance to the sustainability aspects in their food buying decisions [31]. For instance, since the concern for environmental protection and food safety aspects has increased, many quality food characteristics have been associated with what takes place on farms and in the distribution chain ("from farm to fork") and how crops and livestock husbandry were run [32][33][34].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Product characteristics used by consumers to define food quality are not only numerous, but also dynamic, changing according to consumers' interests, concerns, needs, or knowledge. During recent years, consumers started to assign higher importance to the sustainability aspects in their food buying decisions [31]. For instance, since the concern for environmental protection and food safety aspects has increased, many quality food characteristics have been associated with what takes place on farms and in the distribution chain ("from farm to fork") and how crops and livestock husbandry were run [32][33][34].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The Italian version of HTAS, previously described by Saba et al, [27], was applied to investigate subjects' food-related attitudes. This questionnaire consists of three health subscales (a total of 20 items) and three taste subscales (a total of 18 items), and each subscale is composed of an equal number of positively and negatively worded statements [28].…”
Section: Health and Taste Attitude Scale (Htas)mentioning
confidence: 99%
“…This questionnaire consists of three health subscales (a total of 20 items) and three taste subscales (a total of 18 items), and each subscale is composed of an equal number of positively and negatively worded statements [28]. The "Pleasure" subscale was not considered in the present study, since previous results obtained in large population studies demonstrated a very low internal reliability of this subscale in Italian subjects [27,29]. Participants were asked to rank the extent to which each statement corresponded to them, and all items were scored on seven-point Likert scales ranging from "strongly disagree" (score 1) to "strongly agree" (score 7).…”
Section: Health and Taste Attitude Scale (Htas)mentioning
confidence: 99%
“…The multidimensionality of the importance of naturalness for consumers has been discussed by a number of scholars, who have identified a wide range of attributes used for measuring this concept [6,8,13,[32][33][34][35][36][37], leading to a lack of consensus about its definition [6].…”
Section: Food Naturalness and Millennials' Behaviormentioning
confidence: 99%
“…In addition to the absence or presence of certain ingredients, Román et al [9] also considered the production process in the "how the food in produced" category, which includes the degree of "processing" (8) and the use of "traditional" methods (9) in its preparation. A high degree of food processing is commonly associated with foods being more "unnatural and full of chemicals" ( [50], p. 683) and with consumers becoming suspicious about the final product because they do not know the ingredients used in the preparation of the food [33]. Furthermore, the use of "traditional" production methods is viewed as an "old-style" home-made family-farm food production that respects and accepts local customs [51][52][53].…”
Section: Food Naturalness and Millennials' Behaviormentioning
confidence: 99%